Interactions between neutrophils and T-helper 17 cells - Fan, Xinzou; Shu, Panyin; Wang, Ying; Ji, Ning; Zhang, Dunfang (Frontiers in Immunology, 2023)
Neutrophils comprise the majority of immune cells in human peripheral circulation, have potent antimicrobial activities, and are clinically significant in their abundance, heterogeneity, and subcellular localization. In the past few years, the role of neutrophils as components of the innate immune response has been studied in numerous ways, and these cells are crucial in fighting infections, autoimmune diseases, and cancer. T-helper 17 (Th17) cells that produce interleukin 17 (IL-17) are critical in fighting infections and maintaining mucosal immune homeostasis, whereas they mediate several autoimmune diseases. Neutrophils affect adaptive immune responses by interacting with adaptive immune cells. In this review, we describe the physiological roles of both Th17 cells and neutrophils and their interactions and briefly describe the pathological processes in which these two cell types participate. We provide a summary of relevant drugs targeting IL-17A and their clinical trials. Here, we highlight the interactions between Th17 cells and neutrophils in diverse pathophysiological situations.